Banning Black Gods : Law and Religions of the African Diaspora - Boaz, Danielle N. (Book collections on Project MUSE., 2021)
"Examines the global legal challenges faced by adherents of the most widely practiced religions of the African diaspora in the twenty-first century, including Santeria/Lucumi, Haitian Vodou, Candomble, Palo Mayombe, Umbanda, Islam, Rastafari, Obeah, and Voodoo"--